ANALISIS KEBERLANJUTAN PERKEBUNAN KELAPA SAWIT SWADAYA DI KECAMATAN SEKERNAN KABUPATEN MUARO JAMBI - Muhammad Farandika Akbar; Dompak MT Napitupulu; Mirawati Yanita (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
This study aims to determine the general description of smallholder palm oil in Sekernan District, Muaro Jambi Regency, and analyze their sustainability status and sensitive attributes that affect them. The method used in this study is descriptive qualitative and quantitative analysis to determine the status of the sustainability index of smallholder palm oil using MDS Rapid Apparasial analysis, which is modified to RAP-PalmOil, and leverage analysis is used to determine its sensitive attributes. This research was conducted in Suko Awin Jaya, Bukit Baling, Tantan, and Tunas Mudo villages. The sampling location in this study was determined purposively (purposive) with a sample of 100 respondents, who were then determined by simple random sampling. The study results show that the sustainability status of smallholder palm oil in Sekernan District is multidimensionally considered quite sustainable. The economic dimension provides the highest sustainability index and is followed by the social and ecological dimension, which is considered quite sustainable. The sensitive attribute or attribute that has the most influence on the sustainability index value on the ecological dimension is the fertilization period, while the economic dimension is farming income, and the sensitive attribute on the social dimension is conflict resolution